Where are Our Educators? - Елізабет Тюнс; Зоя Рібейро Престес (Preschool Education: Global Trends)
In the present article we aim to examine some effects of social networks on human life. We describe events that were already analyzed by a few authors (Illich, 2006; Bartholo, 1986; Clarke, 2001; Fisher, 2023 and other). For exempl, a confessed Manichaeism was present in the initial vision of Max Fisher – a reporter for the New York Times – regarding social networks and digital platforms, as he himself declared in the book The Chaos Machine (Fisher, 2023), which he published in 2022, translated into Portuguese, in 2023. Like many, at the beginning, he assumed that the dangers of social media came mainly from inappropriate use by malicious people – propagandists, spies, spreaders of fake news – and that, at worst, the platforms were a passive pipeline where the existing problems in society ran. We have known for a long time that the tools we create shape our psyche and are even at the origin of many psychological functions that we highly value. We also know that some tools engender actual cultural transformations (in this regard, see, for example, the social and cultural transformation caused by the invention of alphabetical order in Illich (2002). Despite this, it is curious to note that we behave as if we were immune to the effects of the instruments we create, refusing to admit that they can bring about true revolutions, whether on a cultural level or at the individual level of our psychological structure and functioning. We try to outline short and medium-term effects on people’s relationships and their consequences for individual mental functioning and structure, as well as possible repercussions and consequences for political and social life. We try to outline possible consequences of this new way of life on intellectual and personality development of children and we also manifest our surprise at the absence of our educators in the debate on this issue.